ADSORPTION ISOTHERM STUDY FOR THE REMOVAL OF NICKEL IONS FROM AQUEOUS SOLUTION USING THERMAL POWER PLANT FLY ASH - Agarwal, A; Muthreja, I; Kadu, M; Pandhurnekar, C (MATTER: International Journal of Science and Technology, 2017)
In the present study, the adsorption of nickel ions on the surface of fly ash was investigated. The batch adsorption experiments were performed at constant room temperature 25±10C using Atomic Absorption Spectroscopy (AAS) Technique. Three adsorption isotherms such as Temkin, Harkins Jura and Brunauer-Emmett-Teller (BET) were used to analyze the results obtained from the experiments. The coefficient of correlation (R2) was determined for each isotherm model to establish the best fit adsorption isotherm model. To carry out the error analysis of the three adsorption isotherm models Chi-square test (Ʃχ2) was used. It was concluded from the laboratory investigations and analysis that BET adsorption isotherm is best-fit adsorption isotherm as per linear coefficient of correlation and by nonlinear Chi-square test.